Photocatalyst composite and photocatalytic reaction method using the same
The integration of a bismuth vanadate semiconductor photocatalyst with a porous glass particle carrier addresses the challenges of water decomposition by enhancing photocatalytic activity and handling, achieving efficient light energy conversion for applications in artificial photosynthesis and environmental purification.
Patent Information
- Application Number
- JP2020180748
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-10-28
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2040-10-28
AI Technical Summary
Existing technologies for water decomposition using photocatalysts face challenges in achieving efficient water decomposition due to limitations in photocatalyst combinations that meet the necessary band gap conditions for visible light responsiveness.
A photocatalytic complex is developed using a porous glass particle carrier with a specific surface area of 12 to 240 cm^2/g, immobilizing a bismuth vanadate semiconductor photocatalyst. This configuration enhances handling and photocatalytic activity, allowing for efficient light energy conversion in artificial photosynthesis.
The proposed photocatalytic complex improves handling and achieves high photocatalytic activity, enabling efficient light energy conversion and effective water decomposition, with applications in artificial photosynthesis, air and water purification, and other industrial uses.
Smart Images

Figure 0007662322000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a photocatalyst complex and a photocatalytic reaction method using the same, and relates to a photocatalyst complex that is suitably used for photoreduction of an oxidizer or reductant in water and for carrying out a photocatalytic reaction involving an oxidation reaction of water, and a photocatalytic reaction method using the same, although not particularly limited thereto. [Background technology]
[0002] Compounds such as titanium oxide are known to exhibit catalytic activity when irradiated with light, and are called photocatalysts. One of the catalytic actions is the oxidative decomposition action that oxidizes organic matter on the photocatalyst surface and breaks it down into CO2, H2O, etc. Using this property, product development is underway that aims to purify the environment by deodorizing, removing VOCs, removing dirt, and promoting antibacterial and sterilizing properties by oxidizing and decomposing harmful substances in the environment into harmless substances. Examples include tiles that have antibacterial properties due to the addition of photocatalysts, and air purifiers that break down harmful substances in the air using photocatalysts supported on air filters.
[0003] Also, a water splitting technology that utilizes catalytic action is expected. This technology uses light energy and a photocatalyst to split water and generate hydrogen and oxygen, and is expected to be an artificial photosynthesis technology. Specifically, by irradiating the photocatalyst with energy equal to or greater than the band gap, electrons in the valence band of the photocatalyst are excited to the conduction band, generating electrons in the conduction band and holes in the valence band. The holes oxidize water to generate oxygen and protons [called the "oxygen generation system"; reaction formula (1) below], while the electrons reduce the protons to generate hydrogen [called the "hydrogen generation system"; reaction formula (2) below]. 2H2O → O2+ 4H + + 4e - (1) 4H + + 4e - → 2H2···(2)
[0004] Most water splitting technologies are based on a mechanism in which oxygen and hydrogen are generated simultaneously on one type of photocatalyst (hereinafter referred to as the "single-step mechanism"). In the case of this single-step mechanism, the essential conditions for the photocatalyst are that the valence band of the photocatalyst is more positive than the oxidation potential of water (+1.23 V) and that the positive holes have the potential to oxidize water and generate oxygen, and that the conduction band of the photocatalyst is more negative than the reduction potential of water (0 V) and that the excited electrons have the potential to reduce water and generate hydrogen. However, the conductor of the visible light-responsive photocatalyst is more positive than the reduction potential of water, so water cannot be reduced. In the single-step mechanism, there are usually no photocatalysts that satisfy the above essential conditions, making water splitting difficult.
[0005] One method to improve the visible light responsiveness problem of the one-step mechanism is a two-step mechanism called the "Z scheme," which divides oxygen generation and hydrogen generation into two types of photocatalysts and connects them with an oxidation-reduction complex. In the Z scheme, in the oxygen generation system, holes oxidize water to generate oxygen, and at the same time reduce the oxidized form of the oxidation-reduction complex to generate a reduced form. On the other hand, in the hydrogen generation system, excited electrons reduce water to generate hydrogen, and at the same time oxidize the reduced form of the oxidation-reduction complex to generate an oxidized form. The redox potential of the redox complex must be more positive than the conduction band of the oxygen generation system and more negative than the valence band of the hydrogen generation system. Visible light responsive photocatalysts whose conduction band is more positive than the reduction potential of water can be used in the oxygen generation system if the valence band is more positive than the oxidation potential of water. However, the combination of two types of photocatalysts that satisfy the above essential conditions is limited, which makes water splitting difficult.
[0006] Another form of the two-step mechanism is the photocatalytic / electrolytic hybrid type. Electrolysis is easy to use to generate hydrogen from water, but it requires a large voltage. The photocatalytic / electrolytic hybrid type can generate hydrogen from water at the minimum required voltage by supplementing the hydrogen generation system with electrical energy. In the photocatalytic / electrolytic hybrid type, the photocatalytic electrode and the hydrogen generation electrode are electrically connected in series via an external power source. In the photocatalytic oxygen generation system, the positive holes oxidize water to generate oxygen and electrons, and a voltage is applied by the external power source so that the potential becomes more negative than the reduction potential of water, and in the hydrogen generation system, the hydrogen generation electrode, water is reduced to generate hydrogen.
[0007] Another form of photocatalysis / electrolysis hybrid is Fe 3+ / Fe 2+ In the first step, Fe 3+ When light is irradiated onto the photocatalyst in an aqueous solution, the water is oxidized by the positive holes to produce oxygen and protons, and the electrons oxidize the Fe 3+ is reduced to Fe 2+ is produced, and in the second stage Fe 2+ The aqueous solution was electrolyzed to produce Fe 3+ There are methods for generating hydrogen using this method (see Patent Documents 1 and 2).
[0008] Among these, photocatalysts include titanium oxide (TiO2), tungsten oxide (WO3), iron oxide (Fe2O3), tin oxide (SnO2), zinc oxide (ZnO), strontium titanate (SrTiO3), cadmium sulfide (CdS), zirconium oxide (ZrO2), etc., with titanium oxide being the one that is mainly in practical use.
[0009] On the other hand, Fe 3+ / Fe 2+ In the water splitting process using Fe as a redox agent, one of the main problems with the conversion efficiency is the low conversion efficiency of light energy in the visible region. Since sunlight, which is the main source of light energy, contains only about 3% of light energy in the ultraviolet region, it is extremely important to utilize visible light. For this reason, visible light-responsive photocatalysts are being developed. 3+ / Fe 2+As a photocatalyst for use in a photocatalysis / electrolysis hybrid type with 1,2-dichlorophenyl ether as a redox agent, it has a high visible light response and is highly reactive to oxygen and Fe. 2+ Due to its high production efficiency, bismuth vanadate (BiVO4) is expected to be a photocatalyst for artificial photosynthesis (see, for example, Patent Document 3).
[0010] When BiVO4 is used industrially, it is desirable to fix it on a solid transparent support rather than as a powder, from the viewpoint of ease of handling. Therefore, for example, a bismuth vanadate laminate has been disclosed in which a substrate is placed in a precursor solution containing a vanadium salt and a bismuth salt, and a bismuth vanadate layer is formed on the substrate by a microwave-assisted chemical bath deposition method (see Patent Document 4). This laminate is expected to be applied to a photoelectrode. However, this method is limited to substrates that can be heated by microwaves, such as a glass substrate having an FTO film, and it is difficult to apply a support with a higher transparency. In addition, since it is a flat support, the amount of photocatalyst supported is not sufficient. In addition, a yellow pigment is known that has protruding bismuth vanadate crystals on the surface of a flaky substance such as glass flakes coated with titanium oxide (see Patent Document 5). This is obtained by adding a flaky substance to an acid solution containing bismuth and vanadium to form a suspension, and then adding an alkaline aqueous solution to mature it. However, this is intended to ensure the saturation as a pigment, and there is no disclosure in terms of improving the photocatalytic ability or ease of handling. [Prior art documents] [Patent documents]
[0011] [Patent Document 1] Japanese Patent Application Publication No. 11-157801 [Patent Document 2] JP 2001-233602 A [Patent Document 3] JP 2017-100057 A [Patent Document 4] International Publication WO2014 / 136783 [Patent Document 5] JP 2004-155876 A Summary of the Invention [Problem to be solved by the invention]
[0012] In other words, when using BiVO4 as a photocatalyst for artificial photosynthesis, etc., it is important to achieve both ease of handling and high photocatalytic activity, but conventional technology is still insufficient. As a result of extensive research, the inventors discovered that the above problems could be solved by supporting BiVO4 on a porous glass particle carrier formed from a plurality of glass particles, and thus completed the present invention. [Means for solving the problem]
[0013] That is, the present invention provides a porous glass particle carrier formed of a plurality of glass particles and a photocatalyst made of a bismuth vanadate semiconductor, the photocatalyst being present together with the glass particle carrier, and the specific surface area of the glass particle carrier being 12 to 240 cm 2 / g. In the present invention, a photocatalyst made of a bismuth vanadate semiconductor is used, but it may be called simply a photocatalyst instead of a BiVO4 photocatalyst.
[0014] The glass particle carrier is preferably a glass particle sintered body in which glass particles are sintered together and integrated, or a glass particle aggregate in which a plurality of glass particles are contained in a container and the glass particles are adjacent to each other.
[0015] The glass particles forming the glass particle carrier preferably have an average particle size of 0.1 to 2 mm.
[0016] Furthermore, it is preferable that the photocatalyst is present together with water as a photocatalyst dispersion liquid, and the glass particle carrier is immersed in the photocatalyst dispersion liquid to form a photocatalyst composite. In this case, at least a part of the photocatalyst is present in the voids in the porous glass particle carrier.
[0017] Furthermore, the present invention relates to a photocatalytic reaction method, characterized in that a porous glass particle carrier formed of a plurality of glass particles is immersed in a photocatalytic reaction solution containing a photocatalyst made of a bismuth vanadate semiconductor, an oxidation-reduction agent, and water, and the photocatalytic reaction device is irradiated with light to reduce the oxidation-reduction agent in the photocatalytic reaction solution and to carry out a photocatalytic reaction involving an oxidation reaction of water. Effect of the Invention
[0018] By using the photocatalyst composite of the present invention, for example, when BiVO4 is used as a photocatalyst for artificial photosynthesis, the handling property can be improved and high photocatalytic activity can be achieved. Therefore, it becomes possible to carry out a photocatalytic reaction while increasing the conversion efficiency of light from solar energy.
[0019] In particular, the photocatalytic composite of the present invention can effectively inhibit the oxidation of Fe in water. 3+ / Fe 2+ In the photoreduction reaction of redox species, oxygen and Fe are easily handled and are highly efficient. 2+ can be obtained. In addition to the above photoreduction reaction, the present invention can be suitably used in artificial photosynthesis technology such as reduction of carbon dioxide and hydrogen generation by water decomposition. Furthermore, the present invention can be applied to technologies such as air purification, water purification, antibacterial and sterilizing, and antifouling and antifogging, and can be applied to, for example, residential exteriors, residential interiors, electrical products, vehicles, roads, agriculture, water treatment, soil treatment, air treatment, and medical fields. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] The present invention will be described in detail below.
[0021] The photocatalyst composite of the present invention comprises a porous glass particle carrier formed of a plurality of glass particles and a photocatalyst made of a bismuth vanadate semiconductor, and this photocatalyst is present together with the porous glass particle carrier.
[0022] Of these, the glass particle carrier has a specific surface area of 12 to 240 cm2 / g. A more preferable lower limit of the specific surface area is 16 cm 2 / g, more preferably 20 cm 2 On the other hand, a more preferable upper limit is 120 cm 2 / g, more preferably 80 cm 2 / g. The specific surface area can be measured by image analysis in both the case of a glass particle sintered body and a glass particle aggregate, as described below. Specifically, for example, an SEM image is taken under the conditions described below. If the average particle size obtained from the image is D and the density of the glass particle material is ρ, the volume V of one glass particle is V = (4 / 3)π(D / 2) 3 The surface area S of one glass particle is expressed as S = 4π(D / 2) 2 Therefore, the specific surface area (surface area per unit mass) S m is S m =S / (ρV).
[0023] Furthermore, the shape of each glass particle forming the glass particle carrier is not particularly limited, and examples thereof include spherical, elliptical, cylindrical, angular, plate-like, needle-like, etc. Among these, from the viewpoints that the glass particle carrier is easily formed into a porous shape, numerous holes can be formed in the glass particle carrier, and light irradiated from the outside can be transmitted to its deep portions, it is preferable that the shape of each glass particle is spherical or elliptical.
[0024] Furthermore, the material of the glass particles is preferably light-transmitting, in consideration of irradiating the photocatalyst attached to the surface of the glass particle carrier with light to carry out a photocatalytic reaction. In this case, assuming sunlight as a suitable light source, it is preferable that the material has light transmittance not only for ultraviolet light but also for visible light, and therefore it is preferable that the material has a transmittance of at least 50% for light with a wavelength of 400 nm to 800 nm. Specifically, for example, inorganic materials such as quartz glass, borosilicate glass, soda-lime glass, and alkali-free glass, or resin materials having light transmittance such as acrylonitrile-styrene, polyethylene terephthalate, and polyethylene can be mentioned, but are not limited to these. As will be described later, when a glass particle sintered body is used as the glass particle carrier, soda-lime glass or borosilicate glass is preferable because the sintering temperature during the preparation of the sintered body can be lowered. The transmittance is the ratio of the intensity of light incident at a certain wavelength to the intensity of the light after passing through a material having light transmittance. In addition, in the present invention, light other than sunlight may be used to carry out a photocatalytic reaction.
[0025] Furthermore, the average particle size of the glass particles is preferably 0.1 to 2 mm from the viewpoint of further increasing the reaction efficiency in the photocatalytic reaction using the photocatalytic composite. Among these, a more preferable lower limit of the average particle size is 0.2 mm, and more preferably 0.3 mm. If the average particle size of the glass particles is less than 0.1 mm, there is a disadvantage that the light does not penetrate deep into the glass porous carrier and is scattered on the surface. Furthermore, if the lower limit of the average particle size is within the above range, holes of a suitable size can be formed in the glass particle carrier, and the glass particle carrier can have a suitable surface area, and a sufficient amount of BiVO4 can be present on the surface (including the inside of the holes) of the glass particle carrier. Furthermore, the durability of the obtained glass particle carrier can be ensured. On the other hand, a more preferable upper limit of the average particle size is 1.5 mm, and more preferably 1.2 mm. If the average particle size of the glass particles exceeds 2.0 mm, there is a disadvantage that the photocatalyst aggregates in the holes of the glass porous carrier, and the photocatalytic activity is not exhibited. The average particle size refers to the value of the circle-equivalent diameter not only when the glass particles have a spherical or elliptical shape, but also when the glass particles have other shapes. In the following explanation, the glass particles having a spherical or elliptical shape are preferred, but the explanation for other shapes will also be interpreted as being based on the circle-equivalent diameter.
[0026] The average particle size of the glass particles can be determined, for example, by selecting 200 arbitrary glass particle images from an SEM (scanning electron microscope, magnification = 50 to 200 times) image of the glass particles, regarding the circumscribing circle of the glass particles as the diameter, and calculating the number-average diameter (= the sum of the diameters of each particle ÷ 200).
[0027] On the other hand, the glass particle carrier is not particularly limited, but is preferably a glass particle sintered body in which glass particles are sintered together to form a single body, or a glass particle aggregate in which a plurality of glass particles are contained in a container and the glass particles are adjacent to each other, either of which is a porous body having a large number of pores inside (i.e., in the gaps between the glass particles).
[0028] Although there is no particular limitation on the method for obtaining the glass particle sintered body, it can be preferably produced as follows. First, a mold such as a cylindrical tube and a plate material to be placed thereunder are prepared. These are not particularly limited as long as they are heat resistant, and for example, alumina, stainless steel, titanium, etc. can be used. Next, the mold is placed on the plate material, and glass particles are charged into the mold. At that time, the upper surface is made horizontal so that the glass particles are packed as densely as possible. By sintering the glass particles in this state, the glass particles are fused to each other and sintered. In addition, the sintering temperature and time may be any condition that allows the glass particles to fuse together. For example, when soda-lime glass is used, sintering may be performed at 600 to 750 ° C. near the softening point for about 5 minutes to 4 hours depending on the particle size. If the firing temperature is high and the sintering time is long, the glass particles are fused more firmly, but the porosity tends to be smaller.
[0029] On the other hand, the glass particle aggregate is a glass porous body formed by a plurality of glass particles being accommodated in a container, the plurality of glass particles being filled in a limited space in the container, and the glass particles being in contact with each other and being present in the space. As with the glass particles, the container used here is preferably light-transmitting in consideration of the photocatalytic reaction caused by external irradiation with light, and is preferably light-transmitting not only ultraviolet light but also visible light, and is preferably made of a material with a transmittance of 50% or more for light with a wavelength of at least 400 nm to 800 nm. Specifically, the same material as that of the glass particles can be mentioned.
[0030] In addition, the porosity of the glass particle carrier is preferably 30 to 60% from the viewpoint of further increasing the reaction efficiency in the photocatalytic reaction. Of these, a more preferable lower limit is 40%, and a more preferable upper limit is 50%. In addition, in consideration of the light irradiation to the photocatalyst present on the surface of the glass particle carrier, the thickness of the glass particle carrier is preferably 0.5 to 30 mm. Within this range, the photocatalyst (BiVO4) present in the gaps between the glass particles forming the glass particle carrier can be irradiated with sufficient light, which can contribute to the photocatalytic reaction. In addition, it is also advantageous in terms of ensuring the strength of the glass particle carrier.
[0031] Next, the method of obtaining a photocatalyst composite by placing a photocatalyst made of a bismuth vanadate (BiVO4) semiconductor on the surface of the glass particle carrier as described above is not particularly limited as long as the BiVO4 photocatalyst can be placed on the surface of the glass particle carrier in a state capable of undergoing a photocatalytic reaction. For example, the following method can be exemplified.
[0032] That is, for example, a so-called "impregnation method" can be used in which a powder of BiVO4 photocatalyst is synthesized in advance, and the photocatalyst is present together with water as a photocatalyst dispersion liquid, and a glass particle carrier is immersed in the photocatalyst dispersion liquid to cause the BiVO4 photocatalyst to be attached or present (supported) on the surface of the glass particles forming the glass particle carrier or in the gaps (i.e., voids) between the glass particles; or a so-called "solution method" can be used in which a raw material solution used in the synthesis of BiVO4 is poured into a light-transmitting container forming the glass particle carrier, or into a light-transmitting container in which a glass particle carrier is separately housed, and the container is heated in that state to carry out a synthesis reaction of BiVO4, thereby precipitating (supporting) BiVO4 on the surface of the glass particles. In addition, a powder of a pre-synthesized BiVO4 photocatalyst is mixed with liquid paraffin, polyethylene glycol, etc., and this is placed in a light-transmitting container that forms a glass particle carrier, or in a light-transmitting container in which a glass particle carrier is separately housed, and the photocatalyst is filled in the voids of the glass particle carrier in solid or liquid phase, and after filling, the liquid paraffin, polyethylene glycol, etc. are removed with an organic solvent, thereby forming a paste of the glass particle carrier and the BiVO4 photocatalyst in solid or liquid phase, and causing the BiVO4 photocatalyst to be present (supported) on the surface of the glass particles or in the gaps between the glass particles, a so-called "paste filling method" can be demonstrated. In these methods, a glass particle sintered body can be suitably used as a glass particle carrier in any of the "impregnation method", "solution method" and "paste filling method". On the other hand, a glass particle aggregate is suitably used in the "impregnation method" and "solution method" except for the "paste filling method". In particular, when a glass particle sintered body is used, it can stand on its own, so that it is possible to reduce the size and weight of a photocatalytic reaction device that performs a photocatalytic reaction by forming, for example, a free-standing film.
[0033] In this case, the amount of BiVO4 catalyst supported on the glass particle carrier is preferably 0.005 to 3 mass% relative to the mass of the glass particle carrier. Within this range, the BiVO4 catalyst is uniformly supported without agglomeration, and a high reaction efficiency in the photocatalytic reaction described below can be achieved.
[0034] Here, the method for obtaining the BiVO4 photocatalyst is not particularly limited, and it can be synthesized by using a conventional method.Specific examples include the so-called "suspension method" in which Bi2O3 and V2O5 are stirred in water and concentrated nitric acid is added to precipitate BiVO4, and the so-called "solution method" in which Bi(NO3)3·5H2O and NH4VO3 are separately dissolved in nitric acid to prepare Bi salt solution and V salt solution, which are then mixed, heated, and stirred to precipitate BiVO4.
[0035] Among these, the synthesis method of BiVO4 photocatalyst by the "solution method" will be explained. BiVO4 photocatalyst uses bismuth compounds and vanadium compounds as raw materials. Bismuth compounds are not particularly limited, but include bismuth nitrate (Bi(NO3)3), bismuth chloride (BiCl3), bismuth trioxide (Bi2O3), etc., among which Bi(NO3)3 is preferred. Vanadium compounds are also not particularly limited, but include vanadium pentoxide (V2O5), sodium metavanadate (NaVO3), ammonium metavanadate (NH4VO3), etc., among which NH4VO3 is preferred.
[0036] The bismuth compound and vanadium compound are contained in a solvent, and the concentrations thereof are preferably 15 to 40 mmol / l, more preferably 20 to 35 mmol / l. The molar ratio of bismuth in the bismuth compound to vanadium in the vanadium compound is preferably Bi / V=1 / 1.
[0037] The solvent is not particularly limited as long as the bismuth compound and the vanadium compound can be dissolved in the solvent, but water is preferred, and it is more preferred to add an acid to water. The acid is not particularly limited, but nitric acid, hydrochloric acid, sulfuric acid, perchloric acid, acetic acid, etc. are preferred, and nitric acid is more preferred. The concentration of the acid is preferably in the range of 0.25 to 0.8 mol / l, and more preferably 0.3 to 0.5 mol / l.
[0038] The aqueous precursor solution containing the bismuth salt and the vanadium salt is preferably reacted for 3 to 24 hours at a maximum temperature of 65 to 90° C. More preferably, the reaction time is 24 hours when the maximum temperature is 65° C., and 6 hours when the maximum temperature is 90° C.
[0039] At least one element component selected from the group consisting of Ga, Zn, Ni, Al, and In may be added to the obtained BiVO4. When the element component is added, the ions of these element components, Ga 3+ , Zn 2+ , Ni 2+ , Al 3+ , In 3+ It is preferable to dissolve and mix in the above state. 3+ The amount of addition is preferably within a range of 0.1 to 10 mol %, more preferably 0.2 to 1.0 mol %, based on the substance amount of the bismuth compound or vanadium compound.
[0040] The BiVO4 produced under the above conditions is made of a monoclinic crystal system with a scheelite structure. The average particle size of the BiVO4 photocatalyst is not particularly limited, but is preferably 0.5 to 10 μm.
[0041] On the other hand, a method for synthesizing BiVO4 photocatalyst by the "suspension method" will be explained. BiVO4 photocatalyst uses bismuth compounds and vanadium compounds as raw materials. Bismuth compounds are not particularly limited, but include bismuth nitrate (Bi(NO3)3), bismuth chloride (BiCl3), bismuth trioxide (Bi2O3), etc., with Bi2O3 being preferred. Vanadium compounds are also not particularly limited, but include vanadium pentoxide (V2O5), sodium metavanadate (NaVO3), ammonium metavanadate (NH4VO3), etc., with V2O5 being preferred.
[0042] The bismuth compound and vanadium compound are contained in a solvent, and the concentrations of both are preferably 0.1 to 0.4 mol / l. The molar ratio of bismuth in the bismuth compound to vanadium in the vanadium compound is preferably Bi / V=1 / 1.
[0043] The solvent is not particularly limited as long as the bismuth compound and the vanadium compound can be dissolved therein, but water is preferred, and it is more preferred to add an acid to water. The acid is not particularly limited, but nitric acid, hydrochloric acid, sulfuric acid, perchloric acid, acetic acid, etc. are preferred, and nitric acid is more preferred. The concentration of the acid is preferably in the range of 0.5 to 2.0 mol / l, and more preferably 0.5 to 1.0 mol / l. The liquid temperature is preferably in the range of 60 to 90°C, and more preferably 75 to 85°C.
[0044] At least one element component selected from the group consisting of Ga, Zn, Ni, Al, and In may be added to the obtained BiVO4. When the element component is added, the ions of these element components, Ga 3+ , Zn 2+ , Ni 2+ , Al 3+ , In 3+ It is preferable to dissolve and mix in the above state. 3+ The amount of addition is preferably within a range of 0.1 to 10 mol %, more preferably 0.2 to 1.0 mol %, based on the substance amount of the bismuth compound or vanadium compound.
[0045] The BiVO4 produced under the above conditions is made of a monoclinic crystal system with a scheelite structure. The average particle size of the BiVO4 photocatalyst is not particularly limited, but is preferably 0.5 to 10 μm.
[0046] In the photocatalytic composite of the present invention, when the BiVO4 photocatalyst exists together with water as a photocatalytic dispersion liquid and the glass particle carrier is immersed in this photocatalytic dispersion liquid, the photocatalytic dispersion liquid is made to contain an oxidant, and by irradiating light, a photocatalytic reaction can be carried out in which the oxidant is reduced and water is oxidized (accompanied by an oxidation reaction of water). That is, a photocatalytic reaction device is constructed by immersing a glass particle carrier in a photocatalytic reaction liquid containing a photocatalyst made of a bismuth vanadate semiconductor, an oxidant, and water, and the above-mentioned photocatalytic reaction can be carried out by irradiating light such as an external light source or sunlight.
[0047] Such redox species include Fe 3+ / Fe 2+ , VO2 + / VO 2+ , IO3 - / I - Among them, Fe is the most 3+ / Fe 2+ is preferred.
[0048] Regarding photocatalytic reactions using these redox products, for example, a two-step photoexcitation type photocatalytic reaction called the Z scheme has been reported using iron ion-based redox products (Fe 3+ / Fe 2+ ), it can be expressed as the following formula (3). That is, Fe 3+ Fe 2+ At the same time, water is oxidized to produce oxygen. 2+ The aqueous solution containing the above is taken out of the photocatalytic reaction device and subjected to a separate electrolytic reaction as shown in the following formula (4), thereby producing hydrogen. Photocatalytic reaction: 2H2O+4Fe 3+ →4Fe 2+ +O2+4H + (3) Electrolytic reaction: 4Fe 2+ +4H + →4Fe 3+ +2H2···(4) When this reaction occurs, the solar energy conversion efficiency is Fe 3+ Fe 2+ The photoreduction reaction can be quantified, for example, by colorimetry. EXAMPLES
[0049] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.
[0050] (Examples 1 to 4) <Preparation of BiVO4 photocatalytic composite by filling method> In obtaining the BiVO4 photocatalyst composites according to Examples 1 to 4, first, a BiVO4 photocatalyst was produced by using a suspension method. Specifically, the process is as follows. While stirring 4.66g (10mmol) of Bi2O3, 1.82g (10mmol) of V2O5, 0.04g of Ga(NO3)3·nH2O, and 48ml of water, 2.64ml of concentrated nitric acid (1.42g / ml, 69% by mass) was added. This was heated and stirred at 80℃ for 24 hours. The mixture was cooled to room temperature and filtered to obtain BiVO4:Ga (6.48g, yellow powder).
[0051] The BiVO4 photocatalyst (BiVO4:Ga) obtained above and glass particles of each particle size shown in Table 1 below (material: soda-lime glass, density: 2.5 g / cm 3 The mixture was mixed with 12 g of sucrose and liquid paraffin as a dispersion medium, and filled into a cylindrical glass container (material: borosilicate glass) with an inner diameter of 4 cm and a height of 4 cm. The liquid paraffin was then removed from the glass container by washing with hexane, forming a glass particle aggregate in which glass particles are adjacent to each other in the glass container, and producing a BiVO4 photocatalyst composite in which the BiVO4 photocatalyst is supported on the surfaces of the glass particles in the glass particle aggregate.
[0052] Here, in determining the particle diameter of the glass particles forming the glass particle aggregates in Examples 1 to 4, SEM images of the glass particles used in each Example were taken (50 to 200 times magnification), 200 arbitrary glass particle images were selected, and the circumscribing circle of the glass particle was regarded as the diameter, and the average particle diameter D was calculated as the number-average diameter by dividing the total diameter of each particle by 200. In addition, with regard to the specific surface area of the BiVO4 photocatalyst composite in each Example 1 to 4, the density of the glass particle material was ρ, and the volume V of one glass particle was V=(4 / 3)π(D / 2) 3 The surface area S of one glass particle is expressed as S = 4π(D / 2) 2 Therefore, the specific surface area (surface area per unit mass) S m=S / (ρV). These results are summarized in Table 1. The catalyst loading amount in Table 1 was calculated by subtracting the "mass of the glass particle aggregate and the glass container before loading the BiVO4 photocatalyst" from the "mass of the BiVO4 photocatalyst composite" obtained as described above.
[0053] Example 5 <Preparation of BiVO4 photocatalytic composite by solution method> In obtaining the BiVO4 photocatalyst composite according to Example 5, first, a glass particle sintered body was prepared as a glass particle carrier in the following manner. A titanium foil with a thickness of 50 μm was cut into a strip, and the ends were spot-welded to prepare a mold with a diameter of 4 cm and a height of 1 cm. This mold was placed on an alumina plate, a titanium foil strip with a thickness of 50 μm was wrapped around the inside of the mold, and 12 g of glass particles (material: soda-lime glass) having the particle size shown in Table 1 was charged. The mold filled with glass particles was placed in a sintering furnace together with the alumina plate and sintered. The sintering conditions were 725°C for 1 hour, and the temperature was raised to 725°C over 30 minutes, and then the temperature was held at 725°C for 1 hour. After that, the mold was removed, the strip inside the mold was peeled off, and a glass particle sintered body (12 g) with a diameter of 40 mm, a thickness of 6 to 7 mm, and a porosity of 40 to 45% was prepared.
[0054] Next, 100ml of nitric acid 0.4 mol / l was prepared. 1.5522g (3.2mmol) of Bi(NO3)3·5H2O was weighed into a container. 0.3743g (3.2mmol) of NH4VO3 was weighed into another container. 100ml of the prepared nitric acid was distributed and each was stirred and dissolved to obtain a Bi salt solution and a V salt solution. 0.0064g of Ga(NO3)3·nH2O was added to the dissolved Bi salt solution. The V salt solution was added to the Bi salt solution and mixed. In this way, a mixed solution was prepared.
[0055] Then, as described above, the glass particle sintered body made using glass particles with a number-average diameter of 2.00 mm was placed in a glass container (material: borosilicate glass) with an inner diameter of 4 cm and a height of 4 cm, and 10 ml of the mixed liquid obtained above was placed in this reaction container and heated at 65°C for 24 hours to precipitate BiVO4:Ga. After that, it was cooled to room temperature, filtered, washed with water, and dried to produce a BiVO4 photocatalyst composite.
[0056] Here, the particle size of the glass particles and the specific surface area of the BiVO4 photocatalyst composite were determined in the same manner as in Examples 1 to 4. The catalyst loading amount shown in Table 1 was also the same as in Examples 1 to 4.
[0057] (Comparative Examples 1 to 2) Except for the particle size of the glass particles, BiVO4:Ga obtained by the suspension method and 12 g of glass particles of each particle size and liquid paraffin as a dispersion medium were mixed and filled into a glass container with an inner diameter of 4 cm, as in Example 1. The liquid paraffin was removed by washing with hexane to prepare a BiVO4 photocatalyst composite using a glass aggregate carrier.
[0058] <Evaluation of photocatalytic composite> Each of the BiVO4 photocatalytic composites obtained above was evaluated by photocatalytic reaction as follows. First, 25 μl of 60% HClO4 aqueous solution was added to 150 ml of water at 35°C to adjust the pH. Next, 1.2 ml of 0.25 mol / l Fe(ClO4)3 aqueous solution was added, and the Fe 3+ An aqueous solution containing a redox product (photocatalytic reaction solution) was prepared with a concentration of 2 mmol / l.
[0059] 10 ml of the aqueous solution thus prepared was charged into the BiVO4 photocatalytic composite obtained in the above examples, and a solar simulator (Yamashita Denso YSS-100A) was used to measure 1 SUN (100 mW / cm 2 The solution was then sampled, colored by the phenanthroline method, and the absorbance at 510 nm was measured to determine the amount of Fe 2+The results are shown in Table 1. As can be seen from the results, the glass particles forming the glass particle carrier have an average particle size of 0.1 to 2 mm, and the specific surface area of the glass particle carrier is 12 to 240 cm. 2 / g, photocatalytic activity is exerted.
[0060] [Table 1]
Claims
1. A photocatalyst composite comprising a photocatalyst made of a bismuth vanadate semiconductor present together with water as a photocatalyst dispersion liquid, a porous glass particle carrier formed of a plurality of glass particles and having a specific surface area of 12 to 240 cm2 / g being immersed in the photocatalyst dispersion liquid, the photocatalyst being present within the voids of the glass particle carrier and the photocatalyst being supported on the surface of the glass particle carrier.
2. 2. The photocatalyst composite according to claim 1, wherein the glass particles forming said glass particle carrier have an average particle size of 0.1 to 2 mm.
3. A photocatalytic reaction method comprising the steps of: immersing a porous glass particle carrier formed of a plurality of glass particles in a photocatalytic reaction solution containing a photocatalyst made of a bismuth vanadate semiconductor, an oxidation-reduction agent, and water; and irradiating light onto a photocatalytic reaction device in which a photocatalyst is supported on the surface of the glass particle carrier, thereby reducing the oxidation-reduction agent in the photocatalytic reaction solution and carrying out a photocatalytic reaction involving an oxidation reaction of water.
Citation Information
Patent Citations
Photocatalytic reaction vessel
JP1998015393A
Production of hydrogen by photocatalyst-electrolysis hybrid system
JP1999157801A
System for producing hydrogen comprising semiconductor photocatalyst reacting device and electrolytic device
JP2001233602A
Photocatalyst structure and photocatalyst reactor
JP2002166176A
Yellow pigment
JP2004155876A